Analysis of Economic Value Added (EVA) and Market Value Added (MVA) Methods to Assess Financial Performance (Sub-sector of Food and Beverage Companies Listed on the IDX for the 2017-2021 Period) - Krisdiyanti, Cindy; Sundarta, M. Imam; Hurriyaturrohman (Program Studi Akuntansi Universitas Ibn Khaldun Bogor, 2023)
This study aims to determine and analyze financial performance using the economic value added (EVA) and market value added (MVA) methods in the food and beverage company sub-sector listed on the IDX for the 2017-2021 period. This type of research is qualitative with a descriptive approach. The sampling technique used in this study was purposive sampling of 30 companies, there were three food and beverage companies used as samples. The results showed that the EVA value at PT Akasha Wira International obtained a positive EVA value (EVA> 0) for five years, while at PT Sariguna Primatirta Tbk obtained a positive EVA value (EVA> 0) only in 2019 and 2021 and at PT Indofood CBP Sukses Makmur obtained a positive EVA value (EVA> 0) in 2017-2019 and 2021, this means that the company is able to create economic added value for the company. However, PT Sariguna Primatirta Tbk obtained a negative EVA value (EVA < 0) in 2017, 2018 and 2020, while PT Indofood CBP Sukses Makmur Tbk obtained a negative EVA value (EVA < 0) only in 2020, this means that the company has not been able to create economic added value. The market value added (MVA) value at PT Akasha Wira International Tbk obtained a negative MVA value (MVA < 0) in 2017 and 2018, this indicates that the company was unable to increase the wealth of the company and shareholders. Meanwhile, in 2018-2021, it obtained a positive MVA value (MVA> 0) and at PT Sariguna Primatirta Tbk and PT Indofood CBP Sukses Makmur Tbk obtained a positive MVA value (MVA> 0) for five years, this indicates that the company was able to increase the wealth of the company and shareholders.